A NOVEL STRAIN OF PANTOEA EUCRINA ENDOPHYTE OF MURRAYA KOENIGII WITH SQUALENE CYCLASE ACTIVITY - Nair, Indu M; Jayachandran, K (LIFE: International Journal of Health and Life-Sciences, 2017)
Endophytic microorganisms are potential source of bioactive natural products and contain various enzymes involved in the production of secondary metabolites like cyclic triterpenes. In the present study, medicinal plants producing terpenes were analysed for the presence of the enzyme squalene cyclase. Crude leaf extract of six different medicinal plants were subjected to squalene cyclase assay and the enzyme product formed was subjected to TLC and FTIR analysis. The FTIR representation at 1643 characteristic of the cyclic product, cycloartenol was observed in the TLC scrapped out spot of oxidosqualene treated hexane extract of Murraya koenigii. Further studies on the possible role of endophytes in the induction of squalene cyclase in the selected plant Murraya koenigii resulted in the selection of MKE15 from the four endophytic isolates MKE1, MKE5, MKE15 and MKE18. The PCR based screening for the squalene hopene cyclase (shc) gene was also done to select the potential endophytic strain. The selected endophyte was identified as Pantoea eucrina and is being reported as an endophyte of Murraya koenigii for the first time. The conversion of squalene to the pentacyclic product hopene by the isolate was confirmed by TLC, HPLC, FTIR and GCMS analysis.